Factory production control (FPC) and its requirements for the metallurgical industry - Sz. Pawlak; T. Małysa (Metalurgija, 2023)
The article the requirements of the Factory Production Control (FPC) dedicated to construction products (including metal, i.e. ribbed bars, steel pipes, shapes, sheets and metal constructions) introduced to the single market of the European Union, was presented. Meeting the requirements of legal regulations with regard to these products is an important issue for metallurgical companies placing their products on the EU market. These enterprises are required to effectively implement and supervise the FPC system, supervised by a party independent of the manufacturer (third party). The aim of the article is to present the requirements of the FPC and refer them to the requirements of industry standards for metal products – shapes.